Genome-wide identification and expression profile analysis of TALE superfamily genes under hormone and abiotic stress in maize (Zea may L.) - Guan, Peiyan; Zhao, Dongbo; Wei, Longxue; Cui, Peipei; Zhang, Shicai (Frontiers in Plant Science, 2025)
IntroductionThe three-amino-acid-loop-extension (TALE) of the homeobox superfamily genes plays important roles in plant growth, development, and responses to environmental stress. Although TALE members have been identified in various species, they have not been systematically characterized in maize and their expression profiles under ABA hormone and abiotic stress are unknown.MethodsBioinformatics methods were employed to identify the TALE family genes in the maize genome. The expression levels of ZmTALEs under ABA, salt, drought, and high temperature conditions was detected by qRT-PCR. The subcellular localization of ZmKNOX05 and ZmBELL11 proteins was observed in maize protoplasts.ResultsIn this study, we identified 52 TALE members in maize, which can be divided into two subfamilies, KNOX and BELL. ZmKNOXs and ZmBELLs can be further divided into two subclasses based on the domains they contain. The protein characterizations and gene structures in the same subclass were similar, whereas they were distinct across different subclasses. There were 18 collinear gene pairs in maize genome. Inter-species evolutionary analyses showed that TALE family genes of maize were more homologous to monocotyledons than to dicotyledons. The promoter regions of ZmTALE contained abundant stress-responsive, hormone-responsive, light-responsive, and plant growth and development cis-elements. Specific spatiotemporal expression patterns analysis showed that ZmBELLs were highly expressed in root and mature leaf, whereas the ZmKNOX1 subfamily genes were more expressed in the primordium, internode, vegetative meristem, and root during developmental stages. It was found that most ZmTALEs could respond to ABA, drought, high temperature, and salt stress, indicating their roles in hormone and abiotic stress responsive. ZmKNOX05 and ZmBELL11 were cloned from B73 maize. Unexpectedly, a novel alternative transcript with a 99-base deletion for ZmKNOX05 were found, named ZmKNOX05.2, which exhibited alternative splicing event at the noncanonical site. Subcellular localization analysis revealed that ZmKNOX05.1-eGFP and ZmKNOX05.2-eGFP were localized in both the nucleus and cytoplasm, while ZmBELL11-eGFP was localized in perinuclear cytoplasm (perinuclear region of the cytoplasm).DiscussionWe identified TALE superfamily members in maize and conducted a comprehensive and systematic analysis. These results can lay the foundation for analysis of the functions of ZmTALE genes under ABA and abiotic stresses.